Toward Natural Wound Healing Therapy: Honey and Calendula officinalis Loaded κ-Carrageenan Films with Promising Hemostatic Potential - Jovana S. Vuković; Srđan Perišić; Anja Nikolić; Ivan Milošević; Milorad Mirilović; Bogomir Bolka Prokić; Tijana Lužajić Božinovski (Pharmaceutics)
Background/Objectives: Efficient wound treatment embraces the management of four overlapping phases, starting with hemostasis, an immediate physiological response aimed at stopping bleeding from damaged blood vessels caused by skin injury. This paper proposes an innovative, nature-based hemostatic biomaterial designed to assist natural self-healing regenerative mechanisms. Methods: Light, transparent, and skin-adhesive films based on κ-carrageenan, meadow polyfloral honey, and Calendula officinalis flower extract were fabricated via solution casting. Comprehensive characterization revealed the physicochemical, structural, swelling, and barrier properties and the influence of each bioactive compound utilized for film preparation. Results: The samples subcutaneously implanted in Wistar rats induced vascularization, deposition of collagen, and orientation of collagen fibers while being fully phagocytosed and gradually biodegraded. The rat tail-cut model demonstrated that the films significantly reduced blood loss (0.1875 ± 0.0732 g) compared to the control (0.7837 ± 0.3319 g), and hemostasis was achieved notably faster (355.75 ± 71.42 s) than in the control group (704.25 ± 85.29 s). The rat liver punch biopsy model confirmed reduced blood loss (2.8025 ± 1.5174 g) and shorter time to hemostasis (303.25 ± 77.90 s) compared to the control (3.1475 ± 1.5413 g, 383.00 ± 36.53 s). Conclusions: The results indicate the great potential of the fabricated films as hemostatic wound dressings.